2019
DOI: 10.1123/jsr.2018-0086
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Corrective Exercises on Functional Movement Screen and Physical Fitness Performance in Army ROTC Cadets

Abstract: Individualized corrective exercises improved FMS scores, but did not change physical fitness performance. FMS composite scores and APFT performance are not related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Studying the physical preparation process success of young people makes given study even more relevant and sought-after [3,4]. In this case, the authors' position is coherent with the opinion of foreign experts [1,5,19] in the context of increased motor activity and improving the functional condition characteristics [8,9,20,21]; more successful future professional activities of students [6,7]. The results of our study and other specialists indicate the need for changes in physical education curricula for modern young people [10,11] Improving the physical education of young people in higher educational institutions is aimed at increasing the level of their physical preparation [5,13].…”
Section: Discussionmentioning
confidence: 57%
“…Studying the physical preparation process success of young people makes given study even more relevant and sought-after [3,4]. In this case, the authors' position is coherent with the opinion of foreign experts [1,5,19] in the context of increased motor activity and improving the functional condition characteristics [8,9,20,21]; more successful future professional activities of students [6,7]. The results of our study and other specialists indicate the need for changes in physical education curricula for modern young people [10,11] Improving the physical education of young people in higher educational institutions is aimed at increasing the level of their physical preparation [5,13].…”
Section: Discussionmentioning
confidence: 57%
“…Although the COVID-19 pandemic resulted in poorer home exercise compliance and loss of posttest data points, 45% of females had passing TSPU scores at posttest. Additionally, this study had the second largest female representation in an FMS™ corrective exercise program with twelve subjects completing all FMS™ components compared to previous intervention studies which included four 26 and eighteen 30 females.…”
Section: Discussionmentioning
confidence: 99%
“…While the improvement observed in this study fell short of the hypothesis, 45% (n=9/20) represents a larger proportion of successful performance on the TSPU compared to other literature in female populations. Commonly utilized approaches for improving TSPU performance includes static exercises (ie planks), single plane movements, 27,28,30 or strength training. 27,43 While these studies have shown improvements in total FMS™ score, most of the subjects were males 27,28,43 and multiplanar dynamic trunk stability are largely unaddressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations